Assessment of pottery as a tool for expression and community reintegration in women prisons in Kenya - Otieno, Jane (Research Journal in Advanced Humanities, 2020)
In developed countries, studies have shown that pottery as a form of visual culture encourage self-expression and prepare inmates for release and employment. However, existing studies have failed to investigate pottery in women prisons in Kenya as an effective tool for self- expression and a means to self-reliant. The study aim was to examine pottery as a tool for expression and community reintegration in women prisons in Kenya. The study areas were Lang’ata and Kisii women prisons with a population of 34 respondents. Purposive sampling technique was used to sample 4 illustrators and 30 inmates. The study utilized questionnaire, interview and observation guide to collect data. This study was guided by Vygotsky’s Art and Creativity theory. Descriptive research design guided the study. Using descriptive statistics under the qualitative and quantitative research designs, the study revealed that participants valued the process of creating pottery as a form of expression with age, education and prison confinement being some of the areas that contributed to effective application of images in pottery. The study recommended improvement of facilities in pottery section, retrain of illustrators and encouragement of inmates to intensify on the use of imagery in pottery for self-expression in preparation for successful reintegration.